MicroRNAs in Anticancer Drugs Hepatotoxicity: From Pathogenic Mechanism and Early Diagnosis to Therapeutic Targeting by Natural Products - Atteia, Hebatallah H. (Current Pharmaceutical Biotechnology, 2024)
Patients receiving cancer therapies experience severe adverse effects, including hepatotoxicity, even at therapeutic doses. Consequently, monitoring patients on cancer therapy for hepatic functioning is necessary to avoid permanent liver damage. Several pathways of anticancer drug-induced hepatotoxicity involve microRNAs (miRNAs) via targeting mRNAs. These short and non-coding RNAs undergo rapid modulation in non-targeted organs due to cancer therapy insults. Recently, there has been an interest for miRNAs as useful and promising biomarkers for monitoring toxicity since they have conserved sequences across species and are cellular-specific, stable, released during injury, and simple to analyze. Herein, we tried to review the literature handling miRNAs as mediators and biomarkers of anticancer drug-induced hepatotoxicity. Natural products and phytochemicals are suggested as safe and effective candidates in treating cancer. There is also an attempt to combine anticancer drugs with natural compounds to enhance their efficiencies and reduce systemic toxicities. We also discussed natural products protecting against chemotherapy hepatotoxicity via modulating miRNAs, given that miRNAs have pathogenic and diagnostic roles in chemotherapy-induced hepatotoxicity and that many natural products can potentially regulate their expression. Future studies should integrate these findings into clinical trials by formulating suitable therapeutic dosages of natural products to target miRNAs involved in anticancer drug hepatotoxicity.
Keywords: chemotherapy